PENGARUH KOMPENSASI DAN WORKLIFE BALANCE TERHADAP KINERJA KARYAWAN - Nurlaila; Hayat Yusuf; Feliks Anggia Binsar Kristian Panjaitan; Putu Sumarniwati; Rachmat Rialdy Hasan; Harmiaty Bahar (Jurnal Manajemen dan Kewirausahaan, 2024)
The aim of this research is to test and explain (1) the influence of compensation on employee performance, (2) the influence of work-life balance on employee performance and (3) the influence of compensation and work-life balance on employee performance for Bobong City street sweepers. This type of research uses quantitative descriptive. The population of this research is all street sweepers in Bobong City. The population in this study was 39 people. This research uses a survey approach. Data collection was carried out using a questionnaire. The research results show that compensation has a positive and significant effect on employee performance and work-life balance has a positive and significant effect on employee performance. Furthermore, compensation and work-life balance simultaneously have a positive and significant effect on employee performance. Thus, it can be concluded that changes in increasing compensation and work-life balance which are reflected through benefits and involvement contribute positively simultaneously to increasing employee performance as measured through the aspects of quality, timeliness, effectiveness and independence.